DAMPAK DIMENSI PENGETAHUAN KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PELAKU UMKM - Herman Sjahruddin; Eldi Eldi; Ika Ta’bi; Iva Ta’bi; Semaya Angela Samson (Jurnal Bina Bangsa Ekonomika, 2024)
Financial knowledge is the main element in carrying out business activities, the advice and desire of business actors to continually improve their financial knowledge is the main factor in ensuring business continuity. This study is oriented towards explaining the dimensions of financial knowledge regarding financial management among 53 MSME actors in Mariso District, Makassar City. The sampling technique used a total sampling technique, but there were 23 respondents whose statements were not filled in completely so they could not be used. The test results provide evidence that financial knowledge which is characterized by the dimensions of knowledge of personal finance, knowledge of investment and knowledge of insurance has an effect. which is positive and significant for the financial management of MSME actors, there is only one dimension of knowledge, namely the dimension of knowledge about savings and loans which shows positive results but is not significant in improving the ability of business actors to carry out financial management. These results explain that in general the financial knowledge possessed by MSME actors in Makassar City tends to be high so that it can improve the financial management of MSME businesses.